The combined effect of formic acid and Nisin on potato spoilage. (March 2020) - Ajingi, Ya'u Sabo; Ruengvisesh, Songsirin; Khunrae, Pongsak; Rattanarojpong, Triwit; Jongruja, Nujarin
Abstract: This research has been conducted to investigate the efficacy of formic acid in combination with Nisin against Bacillus subtilis on a potato. To our knowledge, no investigation has evaluated the antimicrobial effectiveness of formic acid in combination with Nisin against Bacillus subtilis in the prevention of potato spoilage, including color changes. Nisin and formic acid inhibited the spoilage organism at 0.016 mg/ml and 0.25% v/v. The susceptibility of the bacteria to Nisin as measured from the diameter of the zone of inhibition was 21 mm, and for formic acid was 18 mm. The combination of Nisin (0.0016 mg/ml) and formic acid (0.025% v/v) inactivated the proliferation of Bacillus subtilis in vitro with a fractional inhibitory index of 0.2 indicating a strong synergistic interaction. 10g of potato samples were inoculated with 10 7  CFU/ml of Bacillus subtilis and treated with Nisin-formic acid combination, 0.02N HCL (Nisin diluent), Nisin, and formic acid for 10 min and stored at 37 °C for 0, 3, 5, 7, and 10 days. After the 10 min treatments and the final storage day, Nisin-formic displayed (5.62–5.37 log reduction) as compared to the control. Formic (0.66–0.05 log reduction), Nisin (0.04–0.07 log reduction), 0.02N HCL (0.43–0.09 log reduction), all displayed significant ( P <5%) inactivity. No significant changes in color were observed with the Nisin-formic treated samples. Therefore, the potential application of synergy between Nisin and formic acid as an antibacterial cocktail in the prevention of potato spoilage is suggested in this report. Highlights: The combined effect between organic acids and the Nisin against each bacterial strains was newly reported. The first report in the use of formic acid with Nisin to prevent proliferation of B. subtilis in potato samples. The MICs of individual and mixture of organic acids and Nisin against B. subtilis and other bacterial pathogenic strains were determined. The susceptibility pattern of bacteria using disk and well diffusions methods was investigated.